Smartphone use and loneliness in life transitions: A biopsychosocial perspective - Behboudi, Afrouz; Knez, Rajna; Andersson, Karl; Larsson, Margaretha; Berglund, Mia; Aberg, Cecilia; Ejeskar, Katarina; Suominen, Sakari; Holford, Dawn; O'Brien, Oonagh; Tognon, Gianluca (SAGE Publications, 2026)
Major life transitions, such as entering the workforce or retirement, often disrupt social ties and increase the risk of involuntary loneliness and social isolation. Smartphone use as a coping strategy during these periods is complex, but particularly relevant for young and older adults, who are especially vulnerable. While smartphones can facilitate social connection, they also carry a substantial risk of problematic use, which has been linked to reduced offline interaction, anxiety, and depression. Clear age-related patterns emerge: young adults more often rely on impulsivity-driven coping (e.g., disordered eating or substance misuse), whereas in older adults, digital engagement more frequently intersects with health-related vulnerabilities, including sleep disturbances, cognitive decline, and gut–brain interactions. Developing a comprehensive biopsychosocial model that integrates biological (e.g., gut microbiota diversity and metabolic markers), psychological (e.g., stress and emotion regulation), and social (e.g., relationships and daily routines) levels of analysis would help distinguish protective from risky digital use. Such an approach could also enable earlier identification of at-risk individuals and support the development of tailored, age-sensitive prevention and intervention strategies during major life transitions.